Impact of the COVID-19 pandemic on early childhood preventive care activities of Office de la Naissance et de l’Enfance (ONE) - Kastrissianakis, Katherina; Bouvy, Anne-Françoise; Goetghebuer, Tessa (Belgian Journal of Paediatrics, 2023)
The Office de la Naissance et de l’Enfance (ONE) is a public organisation overseeing preventive care activities for children within the Wallonia-Brussels Federation. One of the main missions of ONE is to offer free preventive care consultations from birth to the age of 6 years. ONE also issues health recommendations for early childhood day care facilities. The COVID-19 pandemic had a considerable impact on these ONE activities. As events and political decisions unfolded between March and December 2020, actions were taken first to limit children’s consultations to the most essential services like vaccination, and later to facilitate a cautious return to regular activities. After initial difficulties to ensure sufficient doctor presence were addressed, vaccination was successfully pursued. Although many families were supported, delays in follow-up and screening inevitably occurred and constitute a challenge for the future. With regards to day care facilities, protocols were put in place to limit at-risk contacts. Conditions for authorising access to day care were regularly reviewed, and measures to take after a SARS-CoV-2 infection occurrence were regularly adapted in line with national recommendations. Day care facilities were provided with key contact persons within ONE for advice, who were themselves supported by regular updates of recommendations. Broader communication and closer collaboration with doctors working outside ONE were highlighted as critical. This pandemic crisis raised many challenges, yet the commitment and adaptability of professionals within and outside ONE allowed for continuity of preventive care for young children, and contributed to ensuring quality day care